Exploring Conversational and Conventional Implicatures in Sara Bareilles’ Songs: She Used to Be Mine and Brave - Sutrisno, Bejo; Risa, Maya; Rachmawati, Budi (STIBA IEC JAKARTA, 2025)
This study investigates the role of implicature in shaping the interpretation and emotional impact of song lyrics, with a focus on Sara Bareilles’